An experimental study on jatropha-derived alternative aviation fuel sprays from simplex swirl atomizer. (1st September 2016) - Sivakumar, D.; Vankeswaram, S.K.; Sakthikumar, R.; Raghunandan, B.N.; Hu, J.T.C.; Sinha, A.K.
Highlights: Jatropha-derived alternative fuel sprays from simplex swirl atomizer are studied. Spray characteristics of alternative fuels and Jet A-1 are measured. Experimental data of fuel sprays are compared with theoretical predictions. Variation in fuel properties leads to some differences in fuel spray behaviour. Abstract: In assessing the suitability of jatropha-derived alternative aviation fuels for aircraft engines, evaluation of spray characteristics in relation to those of conventional aviation kerosene (Jet A-1) is an important step. The test atomizer employed in the present work is a simplex type hollow cone pressure swirl atomizer used in aircraft engines. The experiments are conducted by discharging fuel spray into quiescent atmospheric air in a fuel spray booth to measure spray characteristics such as fuel discharge behavior, spray cone angle, breakup of liquid fuel sheet and drop size distribution. The characteristics of spray cone angle and fuel sheet breakup are obtained by capturing images of spray using photographic techniques. The measurements of spray drop size distribution are obtained using laser diffraction instrument Spraytec. All the measured spray characteristics of the alternative aviation fuels follow the Jet A-1 both in qualitative and quantitative terms which ensure the drop-in nature of jatropha-derived fuels. The minor differences observed in the comparison of the spray measurements are attributed to the variation in the fuel properties. This claim is supported by the predictions obtained from the theoretical models in literature for the determination of sheet breakup characteristics and mean drop size for sprays discharging from simplex swirl atomizers.